Understanding the Importance of Infection Control Measures among Oral Radiology Patients in Saudi Population - Hanan F. Abdel Maguid; Emad A. Khan (Journal of King Abdulaziz University: Medical Sciences, 2023)
Health-care associated infections are the most common adverse event resulting from medical and dental care. The simplest, most effective measure for preventing healthcare-associated infections is hand hygiene which prevents cross-infection in hospitals. Compliance with recommended instructions is often poor among health care workers. Another indispensable tool for prevention of cross contamination is the use of barrier techniques. This study was conducted to assess the degree of understanding of the importance of infection control measures among patients in a random Saudi population. Moreover, assess their awareness of their rights to demand noncompliant healthcare workers to use those measures for their own protection. 200 patients were randomly chosen from the Oral Radiology Clinic. The patients answered a questionnaire that tested their understanding of the use of infection control methods, as well as their attitude towards their healthcare provider. The results of the questionnaire were tabulated and analyzed. Among male patients, the percentage awareness did not exceed 5%, with degree of awareness less than 15%. Among the female patients they were less than 10% and less than 15%, respectively. Patient awareness or understanding of the importance of infection control measures was far less than expected in the tested population.